HUBUNGAN ANTARA PERSEPSI TERHADAP GAYA KEPEMIMPINAN KHARISMATIK DENGAN KINERJA KARYAWAN - Aprirahmayani, Dwi (Universitas Ahmad Dahlan, 2013)
AbstractThis study aimed to determine the relationship between perceptions of charismatic leadership style to employee performance. Subjects that was used in this study are employees that work in PT. PLN Tarakan in East Kalimantan. The research method used a quantitative research methods. The measuring instruments in this study used Perception Scale Charismatic Leadership Style and the performance appraisal List Value Assessment Performance Employee Performance period 2012 PT. PLN Tarakan Headquarters. The sample of study are 88 participants. The method of data analysis using product moment analysis techniques by using SPSS 16.0 for windows program. The results of the analysis show the value of the product moment correlation rxy = 0.536 with a significance level of p = 0.000 (p <0.000). The contribution of the perceptions of charismatic leadership style on employee performance are 28.7%. Based on the results of data analysis it can be concluded that there is a significant positive relationship between perceptions of charismatic leadership style to employee performance. The higher the perceptions of charismatic leadership style, the higher the employees performance opposite perceptions of charismatic leadership style will also lower the performance of the employees. Keywords: perception charismatic leadership style, employee performance.